2014
DOI: 10.1080/09670262.2014.904524
|View full text |Cite
|
Sign up to set email alerts
|

DNA-based species delimitation in algae

Abstract: Given the problems of species delimitation in algae using morphology or sexual compatibility, molecular data are becoming the standard for delimiting species and testing their traditional boundaries. The idea that species are separately evolving metapopulation lineages, along with theoretical progress in phylogenetic and population genetic analyses, has led to the development of new methods of species delimitation. We review these recent developments in DNA-based species delimitation methods, and discuss how t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
285
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(313 citation statements)
references
References 215 publications
4
285
0
6
Order By: Relevance
“…In phylogenetic studies, gene markers like the SSU rRNA gene, sometimes in combination with other markers, are regularly used to reveal phylogenetic relationships (Jo et al 2013;Škaloud et al 2014). Our results confirm previous results that the SSU offers good phylogenetic resolution on genus level, but is in part too conserved to differentiate between closely related lineages as already reported from different other organisms (Piganeau et al 2011;leliaert et al 2014; showed that the COI region is suitable to distinguish Dinobryon divergens from D. bavaricum strains, which is nearly impossible based on SSU rRNA gene analyses. Our analyses confirmed the high degree of variation for chrysophytes.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In phylogenetic studies, gene markers like the SSU rRNA gene, sometimes in combination with other markers, are regularly used to reveal phylogenetic relationships (Jo et al 2013;Škaloud et al 2014). Our results confirm previous results that the SSU offers good phylogenetic resolution on genus level, but is in part too conserved to differentiate between closely related lineages as already reported from different other organisms (Piganeau et al 2011;leliaert et al 2014; showed that the COI region is suitable to distinguish Dinobryon divergens from D. bavaricum strains, which is nearly impossible based on SSU rRNA gene analyses. Our analyses confirmed the high degree of variation for chrysophytes.…”
Section: Discussionsupporting
confidence: 82%
“…The application of molecular markers for distinguishing protist species and/or assessing diversity patterns in different environments is nowadays an established method (krienitz & Bock 2012;leliaert et al 2014). In phylogenetic studies, gene markers like the SSU rRNA gene, sometimes in combination with other markers, are regularly used to reveal phylogenetic relationships (Jo et al 2013;Škaloud et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, most members of a species should share the same dominant rDNA sequences, assuming our understanding about the mechanism of concerted evolution is correct (Dover, 1986). However, concerted evolution (under a stochastic model) may conservatively maintain the dominant rDNA sequence in the genomes of individuals that form distinct populations which diverged ecologically and evolutionarily long ago (Leliaert et al, 2014). Recent phylogeographic evidence based on independent genetic markers indicate that ITS rDNA can evolve slowly and require many millions of years before nucleotide sequence differences (in the dominant intragenomic variants) arise between two species (Thornhill et al, 2014).…”
Section: S Microadriaticum (A1)mentioning
confidence: 99%
“…This estimated number of species is in agreement with the number of species described for this part of mainland South-east Asia (Thailand, Laos, Cambodia), with some exceptions (see Musser and Carleton 2005), in particular within the Berylmys and Rattus genera or Crunomys diversion. However, regardless of the method used, species delimitation depends on the evolutionary history of the species group and may fail due to incomplete lineage sorting, trans-species polymorphism, hybridisation and introgression (Leliaert et al 2014).…”
Section: Which Reservoir Rodents? Identifying Rodent Species With a mentioning
confidence: 99%